Handbook of fetal medicine - Kumar, Sailesh 1966- (Cambridge University Press, 2010)
Handbook of Fetal Medicine provides a concise and practical guide to the modern management of normal pregnancy and the at-risk fetus. Comprehensive in scope, in an easy-to-use format, the book provides guidance on a wide range of conditions, best practice management strategies and treatment options in maternal-fetal medicine. Each system-based chapter has a brief introduction on embryology and discusses the key genetic developments and relevant developmental abnormalities. The book begins by addressing genetic disorders such as Down syndrome, and goes on to consider skeletal and bodily system abnormalities. All key management points are highlighted and data on long-term outcomes are provided. This book will appeal to maternal-fetal medicine specialists, subspecialty trainees, obstetricians and midwives as a useful practical reference tool in daily practice. It is particularly suitable for trainees in Obstetrics & Gynaecology preparing for the post graduate examinations.